A Machine Learning-Based Approach for Quick Evaluation of Live Simulations in Embodiment Design. (May 2022) - Sauer, C.; Gerschütz, B.; Bernsdorf, J.; Schleich, B.; Wartzack, S.
Abstract: Supporting product developers in early design phases with Live-Simulation can enhance the quality of early product designs. Live-Simulation can also facilitate a democratization of simulation and puts away pressure from simulation experts. In this paper, a machine learning based quick evaluation tool is proposed to support product developers in interpreting Live-Simulation results. The proposed tool enables a quick evaluation of the Live-Simulation results and enables product developers to further enhance their simulations. The tool is shown within a use case in bike rocker switch design.